Kualitas Hidup Penderita Diabetes Melitus Tipe 2 - Arnita, Yuni; Amalia, Riski; Harahap, Inda Mariana (Journal of Telenursing (JOTING), 2023)
This research aims to describe the quality of life of type 2 DM sufferers. The method used is quantitative research using a descriptive design with a sample size of 130 respondents using purposive sampling. Data analysis used univariate tests. The instrument in this research uses DQoL (Diabetes Quality of Life). The results of this research are based on the characteristics of the majority of respondents in the age range 60-69 years (53.84%), female (86.92%), not working (56.15%), high school education (51.54%) , experienced complications (60%), and suffered from DM for around 5-10 years (51.54%), and based on the level of quality of life, the majority of Type 2 DM sufferers were in an unfavorable category (59.23%), while a small percentage others are in the good category (40.77%). In conclusion, the quality of life of Type 2 Diabetes Mellitus sufferers in this study was classified as poor. Keywords: Diabetes Mellitus Type 2, Quality of Life